2007
DOI: 10.1097/01.mat.0000249852.71634.6c
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Bile Acids by Two Different Extracorporeal Liver Support Systems in Acute-on-Chronic Liver Failure

Abstract: Acute-on-chronic liver failure (ACLF) is accompanied by marked intrahepatic cholestasis leading to accumulation of cytotoxic bile acids. Extracorporeal liver support systems efficiently remove bile acids, but their effect on bile acid composition in ACLF is unknown. The aim of the present study was to compare elimination of individual plasma bile acids by albumin dialysis (Molecular Adsorbents Recirculating System, MARS) and fractionated plasma separation (Prometheus). Eight consecutive patients with ACLF unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 38 publications
3
45
0
2
Order By: Relevance
“…However, only MARS has been shown to significantly attenuate hyperdynamic circulation in patients with ACLF [7,34,35].…”
Section: Discussionmentioning
confidence: 99%
“…However, only MARS has been shown to significantly attenuate hyperdynamic circulation in patients with ACLF [7,34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, cholestasis presents with pruritis, renal and pulmonary vascular injury, and hemodynamic changes. Multiple studies have demonstrated the efficacy of albumin dialysis in decreasing total bile acid pool and bilirubin concentration, providing relief of the clinical manifestations of cholestasis [43,44]. MARS treatment could be a useful tool in facilitating hepatic recovery in patients with severe drug-induced liver injury with features of cholestasis, posttransplant cholestasis due to graft dysfunction, and in liver failure patients awaiting transplantation [45,46,47 ].…”
Section: Role Of Nonbiological Devices In Acute-on-chronic Liver Failurementioning
confidence: 98%
“…Once estudios evaluaron el sistema Prometheus s : 6 eran series de casos 23-28 y el resto, ensayos clínicos aleatorizados 15,17,[29][30][31] . No se localizaron estudios que evaluasen la técnica de soporte hepático Prometheus s desde un punto de vista económico.…”
Section: Resultados Estudios Clínicos Incluidosunclassified
“…La prueba de Dersimonian y Laird no mostró evidencia estadística de heterogeneidad (p ¼ 0,1749), y también se observó una reducción no estadísticamente significativa (RR de 0,75 [IC 95% de 0,42-1,35]; p ¼ 0,3427).Sistema Prometheus sLos resultados sobre la supervivencia de los pacientes tratados con el sistema Prometheus s pueden verse en la tabla 3. De los ensayos aleatorizados incluidos, 3 de ellos eran de diseño cruzado y utilizaron los mismos pacientes[29][30][31] . En los 2 ensayos en los que se utilizó grupo control, no se encontraron diferencias significativas en la supervivencia de los diferentes grupos15,17 .Aspectos de seguridadEn varios de los estudios incluidos en esta revisión no se mencionan efectos adversos, y en los que sí lo hacen, parecen ser similares a los del grupo control, con excepción de la trombocitopenia y la hemorragia, que parecen verse incrementadas con el sistema MARS s .…”
unclassified